Proteomic approach for identification of IgA nephropathy-related biomarkers in urine - Prikryl, P; Vojtova, L; Maixnerova, D; Vokurka, M; Neprasova, M; Zima, T; Tesar, V (Physiological research, 2017)
Proteinuria is often used as a surrogate marker in monitoring and predicting outcome in patients with chronic kidney diseases, but it is non-specific. IgAN belongs to the most common primary glomerulonephritis worldwide with serious prognosis. The main aim of this work was to assess differences in urine proteins in patients with IgA nephropathy and to identify abnormal proteins as potential biomarkers of IgA nephropathy or the renal disease. In our pilot project, we selected 20 patients and compared them with 20 healthy volunteers. Protein quantification was performed using iTRAQ (isobaric tag for relative and absolute quantitation) labeling method. The peptides were separated by the isoelectric focusing method (IEF) and nano-LC with C18 column and identified by mass spectrometry using MALDI-TOF/TOF MS. Proteins´ lists obtained from IEF-LC-MS-MS/MS analysis were combined and contained 201 proteins. It was found out that 113 proteins were common in both experiments. 30 urinary proteins were significantly up- or down-regulated in patients with IgA nephropathy. We characterized potential biomarkers such as alpha-1-antitrypsin, apolipoprotein A-I, CD44 antigen or kininogen. Potential biomarkers of IgAN should be validated in further studies.
Keywords: dospělí; Female; IgA nefropatie; apolipoprotein A-I; biologické markery; Biomarkers; Adult; Apolipoprotein A-I; mladý dospělý; ženské pohlaví; lidé; proteomika; Pilot Projects; pilotní projekty; Proteomics; Male; Aged; Young Adult; alpha 1-Antitrypsin; lidé středního věku; senioři; mužské pohlaví; alfa-1-antitrypsin; Middle Aged; Glomerulonephritis, IGA; Humans